2017
DOI: 10.1177/2396941516680369
|View full text |Cite
|
Sign up to set email alerts
|

SLP-educator classroom collaboration: A review to inform reason-based practice

Abstract: Background and aims: Increasingly, speech language pathologists are engaging in collaborative classroom services with teachers and other educators to support children with developmental language disorder and other communication impairments. Recent systematic reviews have provided a summary of only a small fraction of the available evidence and recommended the use of reason-based practice in the absence of a sufficient empirically driven evidence base. The purpose of this paper was to provide a broad (but criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 62 publications
2
59
0
5
Order By: Relevance
“…Collaborative work involves joint planning and decision-making about the priorities and method of delivery of an intervention, and is different from training or directing an assistant where the SLT may take on the role of 'expert'. The aim is often to reduce the functional impact of a child's difficulties on their access to the curriculum, social participation or well-being, and to practise new skills in a range of settings (Archibald 2017).…”
Section: Joint Collaborative Work With Parents And/or Education Staffmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative work involves joint planning and decision-making about the priorities and method of delivery of an intervention, and is different from training or directing an assistant where the SLT may take on the role of 'expert'. The aim is often to reduce the functional impact of a child's difficulties on their access to the curriculum, social participation or well-being, and to practise new skills in a range of settings (Archibald 2017).…”
Section: Joint Collaborative Work With Parents And/or Education Staffmentioning
confidence: 99%
“…Collaborative work between education staff and SLTs may focus on individual children or on whole classes, and systematic reviews have concluded that collaborative work between SLTs and teachers is beneficial in classes with high numbers of 'at-risk' children and also for children with identified language disorders (i.e., across Tiers 1-3) (Archibald 2017, Cirrin et al 2010.…”
Section: Joint Collaborative Work With Parents And/or Education Staffmentioning
confidence: 99%
“…Collaborative work involves joint planning and decision‐making about the priorities and method of delivery of an intervention, and is different from training or directing an assistant where the SLT may take on the role of ‘expert’. The aim is often to reduce the functional impact of a child's difficulties on their access to the curriculum, social participation or well‐being, and to practise new skills in a range of settings (Archibald ).…”
Section: Joint Collaborative Work With Parents And/or Education Staffmentioning
confidence: 99%
“…Collaborative work between education staff and SLTs may focus on individual children or on whole classes, and systematic reviews have concluded that collaborative work between SLTs and teachers is beneficial in classes with high numbers of ‘at‐risk’ children and also for children with identified language disorders (i.e., across Tiers 1–3) (Archibald , Cirrin et al . ).…”
Section: Joint Collaborative Work With Parents And/or Education Staffmentioning
confidence: 99%
“…By working effectively together to plan and deliver supports, SLTs and teachers have the potential to address barriers to learning in school and ultimately to improve language, literacy and educational outcomes for children with DLD (Archibald 2017, Starling et al 2012, Throneburg et al 2000.…”
Section: Introductionmentioning
confidence: 99%